2002
DOI: 10.1023/a:1013585617303
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Desire for healthcare control, health locus of control, perceived control over diabetes, satisfaction with diabetes treatment, and general personality traits were assessed in 54 Type 1 and Type 2 diabetic patients of the same male endocrinologist during a regularly scheduled office visit. At the end of the consultation, both patients and the physician completed a measure describing the interpersonal impacts produced in each by the other's control and affiliation behaviors. Patient success at diabetes control w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Studies proved that HLOC moderated health behaviors and adherence to health treatment plans [3]. Those with high internality had more positive outcomes on their health conditions, while those with low internality and high externality had poor health outcomes and felt less able to control their health and complications of their illnesses [4]- [7]. Others found that patients with high level of internal locus of control had developed effective strategies to control their pain [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies proved that HLOC moderated health behaviors and adherence to health treatment plans [3]. Those with high internality had more positive outcomes on their health conditions, while those with low internality and high externality had poor health outcomes and felt less able to control their health and complications of their illnesses [4]- [7]. Others found that patients with high level of internal locus of control had developed effective strategies to control their pain [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients, caregivers and health professionals vary in their need and desire for authority and control [100] and research has shown that agreement on healthcare responsibilities between patients and health professionals is associated with better health outcomes [101]. We propose that the negotiation of doable tasks and reasonable obligations positively influences cognitive authority and experienced control.…”
Section: Discussionmentioning
confidence: 99%
“…A solid physician-patient communication and relationship is crucial for diagnosis, disease management and control [ 6 9 ] and patient satisfaction [ 10 ]. The first encounter optimally begins with the physician introducing himself to the patient verbally.…”
Section: Discussionmentioning
confidence: 99%